Exposure to thiazole pesticides disrupts pathogens and undermines keystone status of rare taxa within bacterial ecological networks - Minghao Lv; Wenchong Shi; Jie Xu; Shidong He; Lujun Wang; Mingcong Li; Lanxiang Ma; Jiguang Wang; Fengjie Nie; Bingjie Xu; Yifeng Han; Bo Zhou; et al. (Ecotoxicology and Environmental Safety)
Considering the sensitivity of rare microbial taxa to environmental disturbances and their critical roles in ecosystems, it is essential to investigate how soil microbial communities (particularly rare microbes) respond to pesticide exposure. In this study, we found that thiazole pesticides significantly reduced the severity of potato common scab and effectively disrupted the pathogen’s cell membrane integrity. Notably, hierarchical partitioning analysis indicated that the rare microbial taxa in potato geocaulosphere soil constitute key clusters influencing disease incidence. Within bacterial molecular ecological networks, nodes corresponding to these rare taxa generally exhibited higher degrees compared to those of more abundant taxa. However, pesticide exposure reduced the number of keystone nodes and substantially weakened the hub status of rare bacterial taxa in these networks. These findings suggest that, although thiazole pesticides effectively eradicate pathogens, they may also pose a non-negligible potential risk to rare taxa in agricultural ecosystems.